2021
DOI: 10.3390/tropicalmed6010029
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing HIV Drug Resistance among Pregnant Women in Luanda, Angola: Findings from a Cross-Sectional Study

Abstract: The increase in HIV infection and drug-resistant strains is an important public health concern, especially in resource-limited settings. However, the identification of factors related to the propagation of infectious diseases represents a crucial target offering an opportunity to reduce health care costs as well as deepening the focus on preventing infection in high-risk groups. In this study, we investigate the factors related to drug resistance among HIV-infected pregnant women in Luanda, the capital city of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Whereas Sebastião et al studied the factors influencing HIV drug resistance among pregnant females, they found a high frequency of drug resistance among the pregnant HIV females with other comorbidities, living in rural areas, and those with high educational status. 23 Similarly, other studies also confirm that patients' age, residence, education, occupational status, comorbid conditions, and HIV-1 subtypes are the significant factors related to ART failure. 24,25 Limitations of the Study: Among the major limitations of the present study was its crosssectional design and devoid generalizability; these outcomes cannot be generalized for the entire Pakistani population, as the study included only the HIV-positive patients from Peshawar attending the study site for treatment.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 85%
“…Whereas Sebastião et al studied the factors influencing HIV drug resistance among pregnant females, they found a high frequency of drug resistance among the pregnant HIV females with other comorbidities, living in rural areas, and those with high educational status. 23 Similarly, other studies also confirm that patients' age, residence, education, occupational status, comorbid conditions, and HIV-1 subtypes are the significant factors related to ART failure. 24,25 Limitations of the Study: Among the major limitations of the present study was its crosssectional design and devoid generalizability; these outcomes cannot be generalized for the entire Pakistani population, as the study included only the HIV-positive patients from Peshawar attending the study site for treatment.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 85%
“…Previous studies have documented higher rates of STIs and other communicable diseases in Luanda, partly due to the high concentration of risk groups such as sex workers and injecting drug users. [28][29][30][31][32][33] Likewise, studies carried out in Ethiopia and Pakistan also showed that the majority of blood donation candidates with positive serology came from urbanized regions. [34,35] Although not statistically signi cant (p > 0.05), more than 95% of STI and 100% of multiple infections were observed in unmarried subjects, indicating that this group may serve as a potential source of STI dissemination (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Subtypes A and C dominated over other subtypes but all other Env subtypes were present along with untypable basal strains and recombinant strains that prevailed over pure subtypes. The remarkable diversity and evolution of HIV-1 in Angola is driven by the increasing number of new infections 77 , the limited access to antiretroviral therapy, and high levels of drug resistance 46,78 .…”
Section: Discussionmentioning
confidence: 99%